13-15 YOShLI BOKSChILARNI PSIXOLOGIK TAYYORGARLIGIDA MUSOBAQADAGI VAHIMANI YENGISh USULLARI - Ernazarov, G‘.N.; Madjidov, R.R. (SCIENCE and SOCIETY, 2025)
This article analyzes boxers’ psychological preparation and methods for overcoming stress and panic before competitions. It examines the importance of psychological preparation, modern psychological techniques, and their effectiveness in boxing for young men aged 13–15., optimal strategies are proposed for psychological preparation for boxers based on a literature review.